Synthesis and analysis of ZnO and CdSe nanoparticles - Ashtaputre, S. S.; Deshpande, Aparna; Marathe, Sayali; Wankhede, M. E.; Chimanpure, J.; Pasricha, R.; Urban, J.; Haram, Santosh K.; Gosavi, S. W.; Kulkarni, S. K. (Pramana-Journal of Physics, 2005)
Zinc oxide and cadmium selenide particles in the nanometer size regime have been synthesized using chemical routes. The particles were capped using thioglycerol in case of ZnO and 2-mercaptoethanol in case of CdSe to achieve the stability and avoid the coalescence. Zinc oxide nanoparticles were doped with europium to study their optical properties. A variety of techniques like UV-Vis absorption spectroscopy, X-ray diffraction (XRD), photoluminescence (PL), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR) and transmission electron microscopy (TEM) were used to carry out structural and spectroscopic characterizations of the nanoparticles.
1st National Conference on Nanoscience and Technology, Pune, INDIA, MAR 07-08, 2005
Keywords: chemical capping; Doping; Nanoparticles; photoluminescence

Field emission from oriented tin oxide rods - Deshpande, A. C.; Koinkar, Pankaj M.; Ashtaputre, S. S.; More, Mahendra A.; Gosavi, S. W.; Godbole, P. D.; Joag, Dilip S.; Kulkarni, S. K. (Thin Solid Films, 2006)
Tin oxide (SnO2) films were grown on silicon substrates by a wet chemical route. It was found from scanning electron microscopy investigations that oriented SnO2 rods normal to the substrates were obtained. Field emission studies were carried out in diode configuration in an all metal ultra high vacuum chamber at a base pressure similar to 1.33 x 10(-8) mbar. The `onset' field required to draw 0.1 mu A/cm(2) current density from the emitter cathode was found to be similar to 3.4 V/mu m for SnO2 rods. The field emission current and applied field follows the Folwer-Nordheim relationship in low field regime. The observed results indicate that the field emission characteristics of chemically grown SnO2 structures are comparable to the vapor grown nanostructures. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: field emission; microstructures; scanning electron microscopy; tin oxide

Thermally assisted semiconductor-like to insulator transition in gold-poly(methyl methacrylate) nanocomposites - Abyaneh, Majid Kazemian; Pasricha, Renu; Gosavi, S. W.; Kulkarni, S. K. (Nanotechnology, 2006)
Gold-polymethylmethacrylate ( PMMA) nanocomposites were fabricated by mixing gold nanoparticles capped with oleylamine in polymethylmethacrylate. The samples were analysed using UV-vis absorption spectroscopy, transmission electron microscopy, small angle x-ray scattering, Fourier transform infrared spectrometry ( FTIR) and x-ray photoelectron spectroscopy ( XPS). Electrical resistivity of nanocomposite samples was measured by a four-probe technique in the 70-300 K range. The nanocomposites showed a transition with an onset at similar to 160-165 K. They exhibited a semiconductor-like conductivity at higher temperatures and nearly temperature independent conductivity at lower temperatures. The interfacial interaction of Au nanoparticles and PMMA polymer is investigated using FTIR and XPS. A ligand-exchange process occurs when capped gold nanoparticles are incorporated in PMMA polymer.

Low temperature synthesis and NOx sensing properties of nanostructured Al-doped ZnO - Navale, S. C.; Ravi, V.; Mulla, Imtiaz S.; Gosavi, S. W.; Kulkarni, S. K. (Sensors and Actuators B-Chemical, 2007)
Although ZnO is studied intensively as a sensing material, there are limited reports available on aluminum-doped ZnO (AZO) as a NO, sensor. This paper reports selective NO, sensing characteristics of M-doped ZnO synthesized in the form of porous pellets sintered at 350 degrees C. The salient feature of our experimental results is that our sensor can detect small concentrations of NO, at lower operating temperature. It is also observed that as compared to gases such as SOx HCl, LPG, H2S, H-2, ammonia, alcohol and acetone it selectively detects NOx due to Al-doping. The amount of Al in ZnO during synthesis is varied between 1 and 10 wt%. Our sensor senses NO, concentration as low as 20ppm at 100 degrees C with a %response of 11 and a %response of 740 at 300 degrees C for 1 wt% Al. Of all the compositions with Al-doping, I wt% is found to give best results. Sensing experiments carried out at 350 C, however. do not show any significant improvement in the gas sensing properties. The phase contents and lattice parameters were determined by XRD and the average particle size was obtained using Scherrer formula. A probable mechanism for sensing NO, involving oxygen ion adsorption and desorption on the surface of sensor has been suggested. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: aluminum doping; nanomaterial; NOx; Sensor; ZnO

Nitrate reductase-mediated synthesis of silver nanoparticles from AgNO3 - Kumar, S. Anil; Abyaneh, Majid Kazemian; Gosavi, S. W.; Kulkarni, Sulabha K.; Pasricha, Renu; Ahmad, Absar; Khan, Mohammad Islam (Biotechnology Letters, 2007)
Synthesis of silver nanoparticles using alpha-NADPH-dependent nitrate reductase and phytochelatin in vitro has been demonstrated for the first time. The silver ions were reduced in the presence of nitrate reductase, leading to the formation of a stable silver hydrosol 10-25 nm diam. and stabilized by the capping peptide. The nanoparticles were characterized by X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy and UV-Vis absorption. These studies will help in designing a rational enzymatic strategy for the synthesis of nanomaterials of different chemical composition, shapes and sizes as well as their separation.
Keywords: Capping Peptide; enzymatic method; nitrate reductase; silver nanoparticles

Titania nanoparticles synthesis in mesoporous molecular sieve MCM-41 - Lihitkar, N. B.; Abyaneh, Majid Kazemian; Samuel, V.; Pasricha, R.; Gosavi, S. W.; Kulkarni, S. K. (Journal of Colloid and Interface Science, 2007)
Nanocrystalline titanium oxide (TiO2) is one of the most useful oxide material, because of its widespread applications in photocatalysis, solar energy conversion, sensors and optoelectronics. The control of particle size and monodispersity of TiO2 nanoparticles is a challenging task. The use of MCM-41, an inorganic template of uniform pore size (2-10 nm), can overcome this difficulty and produce stable nanoparticles of uniform size and shape. Here, we demonstrate the synthesis of titania nanoparticles inside the pores of silica based MCM-41 forming a TiO2/Si-MCM composite. Composites are formed in the alcoholic medium by incipient wetness impregnation method. Titania particles of average 3 nm size are obtained. Effect of silica and titania precursors on the quality of nanoparticles has been investigated. The characterization of titania-MCM-41 composites has been carried out using a variety of techniques like UV-vis absorption spectroscopy, X-ray diffraction, FT-IR spectroscopy, X-ray photoelectron spectroscopy, transmission electron microscopy and photoluminescence spectroscopy. It has been found that the titania particles are co-ordinated with Si-MCM by Si-O-Ti covalent bond. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: incipient wetness impregnation; Mesoporous material; template; titania

Controlled synthesis of ZnO from nanospheres to micro-rods and its gas sensing studies - Navale, Shalaka C.; Gosavi, S. W.; Mulla, Imtiaz S. (Talanta, 2008)
1D ZnO rods are synthesized using less explored hydrazine method. Here we find, besides being combustible hydrazine can also be used as a structure-directing agent. The ratio of zinc nitrate (ZN) to hydrazine is found to control the morphology of ZnO. At lower concentration of ZN as compared with hydrazine the morphology of ZnO is found to be spherical. As we increase the hydrazine content the morphology changes from spherical (diameter similar to 100 nm) to the elongated structures including shapes like Y, T as well dumbbell (diameter similar to 40 nm and length similar to 150 nm). Interestingly for more than 50% of hydrazine ZnO micro-rods are formed. Such rods are of diameter similar to 120 mn having length of about 1 mu m for ZN to hydrazine ratio of 1:9, isolated as well as bundle of rods are seen in scanning electron microscopy (SEM). The X-ray diffraction (XRD) reveals the phase formation with average particle size of 37 nm as calculated using Scherrer's formula. The high-resolution transmission electron microscopy (HRTEM) is also done to confirm the d-spacing in ZnO. Gas sensing study for these samples shows high efficiency and selectivity towards LPG at all operating temperatures. Photoluminescence (PL) study for these samples is performed at room temperature to find potential application as photoelectric material. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Hydrazine; LPG sensor; Nanostructures; photoluminescence; ZnO

EPR and DRS evidence for NO2 sensing in Al-doped ZnO - Navale, Shalaka C.; Ravi, V.; Srinivas, D.; Mulla, Imtiaz S.; Gosavi, S. W.; Kulkarni, S. K. (Sensors and Actuators B-Chemical, 2008)
Zinc oxide (ZnO) is a well-known semiconducting multifunctional material wherein properties right from the morphology to gas sensitivity can be tailor-made by doping or surface modification. Aluminum (Al)-incorporated porous zinc oxide (AI:ZnO) exhibits good response towards NO2 at low-operating temperature. The NO2 gas concentration as low as 20 ppm exhibits S = 17% for 5 wt. % Al-incorporated ZnO. The NO2 response increases with operating temperature and concentration and reaches to its maximum at 300 degrees C without any interference from other gases such as SO3, HCl, LPG and alcohol. Physico-chemical characterization likes differential thermogravimetric analysis (TG-DTA) electron paramagnetic resonance (EPR) and diffused reflectance spectroscopy (DRS) have been used to understand the sensing behavior for pure and A]-incorporated ZnO. The TG-DTA depicts formation of ZnO phase at 287 degrees C. The EPR study reveals distinct variation for O- (g=2.003) and Zn interstitial (g = 1.98) defect sites in pure and Al:ZnO. The DRS studies elucidate signature of adsorbed NO, species in aluminium-incorporated zinc oxide indicating its tendency to adsorb these species even at low temperatures. This paper is an attempt to correlate the gas sensing behavior with the physico-chemical studies such as EPR and DRS. (c) 2007 Published by Elsevier B.V.
Keywords: aluminum doping; DRS; EPR; NO2 sensor; ZnO

Surface studies on benzophenone doped PDMS microstructures fabricated using KrF excimer laser direct write lithography - Kant, Madhushree Bute; Shinde, Shashikant D.; Bodas, Dhananjay S.; Patil, K. R.; Sathe, V. G.; Adhi, K. P.; Gosavi, S. W. (Applied Surface Science, 2014)
his paper discusses microfabrication process for benzophenone doped polydimethylsiloxane (PDMS) using laser lithography. KrF excimer laser of 248 nm with 20 ns pulse width at repetition rate of 1 Hz was used for microfabrication of undoped and benzophenone doped PDMS. The doped-PDMS shows sensitivity below 365 nm, permitting processing under ambient light. The analysis of etch depth revealed that doped PDMS shows self developable sensitivity at lower fluence of similar to 250 mJ/cm(2). The unexposed and exposed surface was studied using Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and Scanning electron microscopy (SEM). Spectrocopic analysis indicated increase in C-O, C=O, Si-O-3 and Si-O-4 bonding at the expense of Si-C and Si-O-2 bonds of PDMS. In case of laser exposed doped-PDMS, removal of benzophenone from probe depth of spectroscopy was observed. Whereas the surface morphology of exposed and unexposed doped-PDMS was observed to be same, indicating clean development of PDMS micropattems. The present study indicates that addition of 3.0 wt.% benzophenone in PDMS enhance self development sensitivity of PDMS. The self developable results on doped-PDMS are quite encouraging for its potential use in point of care Lab-On-Chip applications, for fabricating micropattems using direct write laser lithography technology.
Keywords: Direct write laser lithography; Microfabrication; micropatterning; Poly(dimethylsiloxane) (PDMS)

Synthesis and luminescence of graphene-nano calcium sulphide composite - Sharma, Geeta; Patil, K. R.; Gosavi, S. W. (Materials Chemistry and Physics, 2014)
Graphene-nanocrystalline calcium sulphide has been synthesized using in-situ reduction of calcium salt and graphene oxide. Graphene oxide was prepared using Hummer's method. Surface morphology and crystal structure of samples were observed by transmission electron microscopy (TEM) and X-Ray diffraction (XRD). Ultra thin graphene and graphene oxide sheets with size ranging between tens to several hundreds of square nanometers are observed in TEM images. The TEM micrographs of G-CaS show that CaS particles are embedded in graphene sheets and the average particle size of CaS particles in the composite is less than 50 nm. The reduction in the intensity of various functional groups in FTIR spectrum also confirms the formation of graphene. The UV-Visible spectra of CaS shows absorption peak at 220 nm with a small shoulder at 250 nm whereas in G-CaS 220 nm absorption peak has reduced intensity and the shoulder at 250 nm has now shifted to 270 nm due to modification in the defect structure of CaS by graphene. CaS and G-CaS shows photoluminescence emission at 470 nm (lambda(exc.) = 375 nm) and 440 nm (lambda(exc.) = 350 nm) respectively, however emission intensity of G-CaS is relatively lower than CaS. Although the emission intensity is found to be lower than CaS, addition of CaS to graphene in G-CaS complex has made graphene luminescent. XPS spectra also indicate reduction of various oxygen containing functional groups in highly reduced graphene oxide and G-CaS. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Luminescence; Nanostructures; powder diffraction; Precipitation

Enhanced energy density and stability of self-assembled cauliflower of Pd doped monoclinic WO3 nanostructure supercapacitor - Gupta, S. P.; Patil, V. B.; Tarwal, N. L.; Bhame, S. D.; Gosavi, S. W.; Mulla, I. S.; Late, D. J.; Suryavanshi, S. S.; Walke, P. S. (Materials Chemistry and Physics, 2019)
Enhanced electrochemical performance of WO3 nanostructures by engineering their morphology, structural and surface defect at nanoscale is feasible. Herein we report the effect of Pd doping on the morphological and electrochemical properties of WO3 at nanoscale prepared by a simple hydrothermal method. The synthesized pristine WO3 (cabbage like morphology) and Pd doped WO3 (cauliflower like morphology) are examined by using XRD, XPS, Raman spectra, BET, FE-SEM, TEM. The morphological investigation shows the effective rebuilding of nanosheets assembled cabbage shaped pristine WO3 into nanobricks assembled cauliflower shaped Pd doped WO3 with improvement in crystallinity, surface area and conductivity. As a result, the enhancement in the electrochemical performance of cauliflower shaped Pd-WO3 is recorded four times higher specific capacitance than pristine WO3. Additionally, the excellent cyclic stability (almost ten times higher than pristine WO3) up to 1100 cycles with nearly 86.95% capacity retention is observed in Pd-WO3 attributed to Pd content and highly modified structural arrangement.